Electrochemical oxidation of 5-hydroxymethylfurfural on ternary metal–organic framework nanoarrays: enhancement from electronic structure modulation. Issue 25 (18th June 2021) - Bai, Xiao-Jue; He, Wen-Xiu; Lu, Xing-Yu; Fu, Yu; Qi, Wei
Abstract : A facile one-step solvothermal strategy has been developed for the in situ growth of ternary MOF nanoarrays onto Ni foam, which exhibits superior electrocatalytic activity and stability for the electrochemical 5-hydroxymethylfurfural oxidation. Abstract : The rational design and exploitation of highly active and stable catalysts for the electrochemical oxidation of biomass-derived 5-hydroxymethylfurfural (HMF) to valuable chemical 2, 5-furandicarboxylic acid (FDCA), is of great significance. Herein, a ternary metal–organic framework nanoarray is in situ hydrothermally deposited on Ni foam via assembling of multiple metal ions (Co 2+, Ni 2+ and Fe 2+ ) and 2-amino-terephthalic acid. The integrated MOF composite can directly act as a catalytic electrode, which exhibits excellent electrocatalytic HMF oxidation activity with a high current density of 100 mA cm −2 at a potential of only 1.35 V vs. RHE. More importantly, the constant potential electrolysis at 1.4 V vs. RHE in combination with chromatographic analysis reveals a high faradaic efficiency close to 100% towards the production of FDCA with a yield of 99.76%. The high electrocatalytic performance for HMF oxidation is attributed to the abundant accessible active sites of two-dimensional morphology and the optimized electronic structure of the intrinsic catalytic centers in MOFs. The present study sheds light on the rational design and synthesis of new MOF-based catalysts for biomass conversion and stimulate the extensive explorations of MOFs with tunable active sites for potential electrocatalysis applications.